Biochemical Screening for Nonadherence Is Associated With Blood Pressure Reduction and Improvement in Adherence. Issue 5 (November 2017) - Gupta, Pankaj; Patel, Prashanth; Štrauch, Branislav; Lai, Florence Y.; Akbarov, Artur; Gulsin, Gaurav S.; Beech, Alison; Marešová, Věra; Topham, Peter S.; Stanley, Adrian; Thurston, Herbert; Smith, Paul R.; et al.
Abstract : We hypothesized that screening for nonadherence to antihypertensive treatment using liquid chromatography-tandem mass spectrometry–based biochemical analysis of urine/serum has therapeutic applications in nonadherent hypertensive patients. A retrospective analysis of hypertensive patients attending specialist tertiary care centers was conducted in 2 European countries (United Kingdom and Czech Republic). Nonadherence to antihypertensive treatment was diagnosed using biochemical analysis of urine (United Kingdom) or serum (Czech Republic). These results were subsequently discussed with each patient, and data on follow-up clinic blood pressure (BP) measurements were collected from clinical files. Of 238 UK patients who underwent biochemical urine analysis, 73 were nonadherent to antihypertensive treatment. Their initial urinary adherence ratio (the ratio of detected to prescribed antihypertensive medications) increased from 0.33 (0–0.67) to 1 (0.67–1) between the first and the last clinic appointments. The observed increase in the urinary adherence ratio in initially nonadherent UK patients was associated with the improved BP control; by the last clinic appointment, systolic and diastolic BPs were ≈19.5 and 7.5 mm Hg lower than at baseline ( P =0.001 and 0.009, respectively). These findings were further corroborated in 93 nonadherent hypertensive patients from Czech Republic—their average systolic and diastolic BPs dropped by ≈32.6 and 17.4 mm Hg, respectively ( P <0.001), on appointments after the biochemical analysis. Our data show that nonadherent hypertensive patients respond to liquid chromatography–tandem mass spectrometry-based biochemical analysis with improved adherence and significant BP drop. Such repeated biochemical analyses should be considered as a therapeutic approach in nonadherent hypertensive patients.